Green vehicle traffic routing system using ant-based algorithm - Jabbarpour, M.R.; Noor, R.M.; Khokhar, R.H. (Elsevier, 2015)
Vehicle traffic congestion leads to air pollution, driver frustration, and costs billions of dollars annually in fuel consumption. Finding a proper solution to vehicle congestion is a considerable challenge due to the dynamic and unpredictable nature of the network topology of vehicular environments, especially in urban areas. Vehicle Traffic Routing Systems (VTRSs) are one of the most significant solutions for this problem. Although most of the existing VTRSs obtained promising results for reducing travel time or improving traffic flow, they cannot guarantee reduction of the traffic-related nuisances such as air pollution, noise, and fuel consumption. Hence, in this paper, we present a green VTRS that reduces fuel consumption and consequently CO2 emissions via ant-based algorithm combined with fuel consumption model. This VTRS is an Ant-based Vehicle Congestion Avoidance System (AVCAS) that uses Signalized Intersection Design and Research Aid (SIDRA) fuel consumption and emission model in its vehicle routing procedure. This approach is called AVCAS +SIDRA which utilizes various criterion such as average travel time, speed, distance, vehicle density along with road map segmentation to reduce fuel consumption as much as possible by finding the least congested shortest paths in order to reduce the vehicle traffic congestion and their pollutant emissions. The proposed approach is evaluated and validated through simulation environment and tools (i.e. NS-2, SUMO, TraNS). Experimental results conducted on three different scenarios (i.e. various vehicle densities, system usage rates and accident condition) considering average travel time, travel speed, travel distance and fuel consumption as evaluation metrics. The obtained results show that the AVCAS + SIDRA outperforms the existing approaches in terms of average travel time, average travel speed and fuel consumption rate, by an average of 25.5%, 19.5% and 17%, respectively. Consequently, our proposed green VTRS alleviates energy consumption as it is not only becoming scarce and expensive but also causing a dramatic climate change and emission. (C) 2015 Elsevier Ltd. All rights reserved.